History of the Department of English (1921-2021): An Academic Overview (Spectrum, 2022)
As the Department of English, University of Dhaka celebrates its centenary in the year 2021, it is vital to look back and take stock of its achievements as well as the challenges it has faced over the years on the way to becoming a premier department for English studies and for English language education in the region. In this paper, we explore the academic history of the department using archival resources and interviews with senior academics who have not only witnessed but also played key roles in the evolution of the department. Based on the available data, we highlight the original motivations of the founders for establishing the department, the key changes in the curriculum and the forces that drove those changes, the academic and administrative structures, the major achievements of its teachers as well as its alumni, and the challenges facing the department today. Overall, the paper provides a few insights which may be useful for those involved in English studies in Bangladesh and other similar historical and social contexts.Spectrum, Volume 16, June 2021: 3-23